2018
DOI: 10.1002/asia.201701697
|View full text |Cite
|
Sign up to set email alerts
|

Drug Self‐Delivery Systems Based on Hyperbranched Polyprodrugs towards Tumor Therapy

Abstract: Amphiphilic hyperbranched polyprodrugs (DOX-S-S-PEG) with drug repeat units in hydrophobic core linked by disulfide bonds were developed as drug self-delivery systems for cancer therapy. The hydroxyl groups and the amine group in doxorubicin (DOX) were linked by 3,3'-dithiodipropanoic acid as hydrophobic hyperbranched cores, then amino-terminated polyethylene glycol monomethyl ether (mPEG-NH ) as hydrophilic shell was linked to hydrophobic cores to form amphiphilic and glutathione (GSH)-responsive micelle of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The drug‐loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent. Duan et al . have recently reported the direct preparation of a hyperbranched polyprodrug by using drug molecules as polymeric monomers with drug‐loading contents of 22 and 24 %.…”
Section: Drug‐delivery Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug‐loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent. Duan et al . have recently reported the direct preparation of a hyperbranched polyprodrug by using drug molecules as polymeric monomers with drug‐loading contents of 22 and 24 %.…”
Section: Drug‐delivery Applicationsmentioning
confidence: 99%
“…[48] The drug-loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent. Duan et al [49] have recently reported the direct preparation of ah yperbranched polyprodrug by using drug molecules as polymericm onomers with drug-loading contentso f2 2a nd 24 %. After self-assembly,t he micelles can be used for drug delivery and have been shown to have ag ood anticancer effect.…”
Section: Drug Conjugation By Using the Drug As Ap Olymeric Monomermentioning
confidence: 99%
“…To overcome these problems, drug self‐delivery systems (DSDSs) have been developed most recently, exhibiting nanoscale characteristic to endow intracellular delivery by themselves without any nanocarriers, as drug–drug conjugates, polymer prodrugs, or molecular hydrogels . Such nano‐DSDSs could release therapeutics or their derivatives by cleaving the conjugating linkages, responding to the acidic media or high reductant level in tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] To avoid this phenomenon in the chemical therapy process, much attention has been focused on polymer-drug conjugates to enhance the poor bioavailability of these chemical drugs. Moreover, the linkage between the polymer and the chemical drug is designed so that it is degradable and responsivet oi ntracellular changes so as to release the drug efficiently.G enerally,s everal stimuli-responsive bonds, [11][12][13][14][15][16] such as imine, hydrazone, disulfide bond, acid-labile acetal, ketal, and carbamate linkages, can be cleavedf rom the polymer under the low pH value conditions of endosomes/lysosomes or the high cellular glutathione (GSH) levels in tumor tissue, thus providing better security in the treatment process. Moreover, the linkage between the polymer and the chemical drug is designed so that it is degradable and responsivet oi ntracellular changes so as to release the drug efficiently.G enerally,s everal stimuli-responsive bonds, [11][12][13][14][15][16] such as imine, hydrazone, disulfide bond, acid-labile acetal, ketal, and carbamate linkages, can be cleavedf rom the polymer under the low pH value conditions of endosomes/lysosomes or the high cellular glutathione (GSH) levels in tumor tissue, thus providing better security in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] These prodrug-based self-assemblies not only protect the hydrophobic drugs from leakage but also can be transformed from their inactive form in an ormale nvironment into their active form in ac ancere nvironment. Moreover, the linkage between the polymer and the chemical drug is designed so that it is degradable and responsivet oi ntracellular changes so as to release the drug efficiently.G enerally,s everal stimuli-responsive bonds, [11][12][13][14][15][16] such as imine, hydrazone, disulfide bond, acid-labile acetal, ketal, and carbamate linkages, can be cleavedf rom the polymer under the low pH value conditions of endosomes/lysosomes or the high cellular glutathione (GSH) levels in tumor tissue, thus providing better security in the treatment process. Although the prodrug-based approach has been demonstrated to be useful for cancert herapy,r esearcherscontinue to be perplexed by the complicated synthesis procedures and preparation methods required forprodrugs.…”
Section: Introductionmentioning
confidence: 99%